(NkOMPLEKSNOE ISSLEDOWANIE sOLNCA I SOLNE^NO(B-(NZEMNYH SWQZEJ (B:s (NtRUDY (BIII (NMEVDUNARODNOGO SOWE]ANIQ (B"(Nkoronas(B-(Ni(B" ((NkALUGA(B, 5-10 (NDEKABRQ (B1988 (NG(B.) /s ((Nl(B. :s (Nfti(B,s, 1989)
(NbIBLIOGR(B. (NW KONCE DOKL(B.s
(N~ASTX TEKSTA NA ANGL(B.s
(Nan sssr(B. (NoRDENA lENINA FIZ(B.-(NTEH(B. (NIN(B-(NT IM(B. (Na(B.(Nf(B. (NiOFFEs
Keywords: (NsOLNE^NO(B-(NZEMNYE SWQZIs; (NsOLNCEs; (NfIZIKAs